Analysis of the Influence of Reproductive Health Education on Adolescent Sexual Behavior in the Tilamuta Community Health Center Work Area - Amelga Tamadu; Retno Dewi Prisusanti (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2025)
This study aims to examine the effect of reproductive health education on adolescent knowledge as an indicator of sexual behavior prevention among students of in the Tilamuta Community Health Center Work Area. This study used a quantitative approach with a pre-post-intervention design involving 30 adolescent respondents. Data were collected through a structured questionnaire that measured respondents' age characteristics and knowledge levels before and after the reproductive health education intervention. Descriptive statistical analysis and frequency distribution were used to describe the respondents' characteristics, while the Wilcoxon Signed Rank Test was applied to analyze differences in knowledge levels before and after the intervention. The results showed that all data were valid with no missing values, and most respondents were aged 15-16 years. Before the intervention, respondents' knowledge levels varied, with the majority classified as having moderate knowledge. After the intervention, all respondents achieved a good level of knowledge, indicating a uniform increase. The Wilcoxon Signed Ranks Test revealed a statistically significant difference between pre- and post-intervention knowledge levels (Z = −4.001; p < 0.000), with no respondents experiencing a decrease in knowledge. These findings suggest that reproductive health education has a significant and positive impact on improving adolescent knowledge, which is crucial for encouraging healthier and more responsible sexual behavior among adolescents.